2022
DOI: 10.1101/2022.03.13.484126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination treatment can hinder the evolution of resistance to antimicrobial peptides

Abstract: Antibiotic resistant microbial pathogens are becoming a major threat to human health. Therefore, there is an urgent need to develop new alternatives to conventional antibiotics. One such promising alternative is antimicrobial peptides (AMPs), which are produced by virtually all organisms and typically inhibit bacteria via membrane disruption. However, previous studies demonstrated that bacteria can rapidly develop AMP resistance. Here, we study whether combination therapy, known to be able to inhibit the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Bacterial resistance to individual AMPs is rare yet possible, 31−34 while bacterial resistance is less probable to AMP−AMP combinations. 23,35 This is one of the reasons why AMP−AMP combinations are more likely to not only be more effective than individual AMPs 36−38 but also serve as long-term antimicrobials in contrast to traditional antibiotics. 39−41 Several possible sources of cooperativity have been proposed.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial resistance to individual AMPs is rare yet possible, 31−34 while bacterial resistance is less probable to AMP−AMP combinations. 23,35 This is one of the reasons why AMP−AMP combinations are more likely to not only be more effective than individual AMPs 36−38 but also serve as long-term antimicrobials in contrast to traditional antibiotics. 39−41 Several possible sources of cooperativity have been proposed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is currently accomplished by using several classes of specific small organic molecules that are generally called antibiotics . However, in the last 30 years, we have witnessed an increasing resistance to antibiotics in bacteria, which threatens to severely decrease our ability to protect human health. These alarming trends stimulated a broad search for novel antibacterial agents and techniques. , Antimicrobial peptides (AMPs), which are produced by multicellular organisms as part of their immune responses to external infections, came out as promising alternatives to antibiotics. Some organisms, e.g., frogs, produce a wide variety of AMPs in their skin secretions. , AMPs are relatively short peptide-chain molecules with typically large fractions of separated positively charged and hydrophobic residues that exhibit activities against multiple classes of bacteria, fungi, viruses, and even cancer. It was also observed that combinations of some specific types of AMPs frequently work much more efficiently than single-type peptides. Although it is known that, in contrast to single AMPs, AMP combinations are less toxic, can better hinder the ability of bacteria to develop resistance, and can associate to bacterial cells faster, the microscopic mechanisms of AMP–AMP cooperativity remain not well understood. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs are relatively short peptide-chain molecules with large fractions of separated positively charged and hydrophobic residues that exhibit activities against multiple classes of bacteria, fungi, viruses, and even cancer [10][11][12][13][14]. It was also observed that combinations of some specific types of AMPs frequently work much more efficiently than single-type peptides [15][16][17][18][19]. Although it is known that AMPs combinations are less toxic, can hinder the ability of bacteria to develop resistance, and can associate to bacterial cells faster, the mechanisms of AMPs cooperativity remain not well understood [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that combinations of some specific types of AMPs frequently work much more efficiently than single-type peptides [15][16][17][18][19]. Although it is known that AMPs combinations are less toxic, can hinder the ability of bacteria to develop resistance, and can associate to bacterial cells faster, the mechanisms of AMPs cooperativity remain not well understood [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%